Low Serum IL-17A in Pregnancy During Second Trimester Is Associated With an Increased Risk of Subclinical Hypothyroidism - He, Leqi; Zhu, Xiuju; Yang, Qian; Li, Xiaoying; Huang, Xinmei; Shen, Chunmei; Liu, Jun; Zha, Bingbing (Frontiers in Endocrinology, 2020)
Problem: Interleukin-17A (IL-17A) has a role in sustaining normal pregnancy. IL-17A is also associated with thyroid autoimmunity during pregnancy.This study sought to investigate whether IL-17A is a risk factor for thyroid dysfunction during pregnancy without thyroid autoimmunity. Methods of study: The study comprised 216 pregnant women with negative thyroid peroxidase antibody (TPOAb) and thyroglobulin antibodies (TGAb) during the second trimester who provided samples for serum IL-17A and thyroid function detection. To further evaluate the ratio of CD4+IL-17A+ Th17 cells, we collected peripheral blood from 26 participants with thyroid-stimulating hormone (TSH) levels ≤2.5 mIU/L and 26 pregnant-week matching populations with TSH levels >2.5 mIU/L, along with samples from 20 participants with TSH levels ≤4 mIU/L and 20 pregnant-week matching populations with TSH levels >4 mIU/L. Results：The serum IL-17A levels and ratios of CD4+IL-17A+ cells were significantly lower in women with TSH >2.5 mIU/L than in those with TSH ≤2.5 mIU/L (both P<0.01). Similar lower differences were noted in women with TSH >4 mIU/L (subclinical hypothyroidism) than in those with TSH ≤4 mIU/L (both P<0.01). The IL-17A level (β=-0.195, P=0.004) and week of gestation (β=0.284, P=0.000) were significant predictors of regression, with TSH as the dependent variable in all participants during the second trimester.Logistic regression indicated that a lower serum IL-17A level was a risk factor for TSH>2.5 mIU/L [OR=0.453 (0.298-0.689), P=0.000] and subclinical hypothyroidism [OR=0.588(0.385-0.899), P=0.013]. Conclusion：A low serum IL-17A level during the second trimester is associated with an increased risk of TSH >2.5 mIU/L and subclinical hypothyroidism .